Kebijakan Moneter Islam Berlandaskan Maqashid Syariah Bagi Pembangunan Berkelanjutan - Amalia Nuril Hidayati; Haeva Zuliani; Novelia Krisgiyanti; Natasya Yulia Vernanda; Ramadhani Endira Aszara (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
In a globalized and uncertain economy, monetary policy is vital for stability and growth. However, prioritizing only prices and interest rates can result in income inequality and a disconnect between financial and real sectors. This study examines Islamic monetary policy's role in supporting sustainable development aligned with the SDGs through a literature review. Islamic monetary policy promotes fairness through principles like the prohibition of interest (riba) and equitable wealth management, utilizing tools like zakat, waqf, and qard al-hasan to foster economic development. Islamic financial instruments are crucial for achieving SDGs, such as poverty reduction and education access. Despite challenges from conventional systems, there are opportunities to advance Islamic monetary policy by enhancing institutions and innovating in finance technology. This research indicates that Islamic monetary policy promotes economic stability, social justice, and sustainable growth.